KEBIJAKAN PENGUNGKAPAN, TRANSPARANSI INFORMASI DAN KUALITAS LAPORAN KEBERLANJUTAN: INDEPENDENSI KOMITE AUDIT SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2022-2024) - Evangelista Ivena Putri; Anis Chariri (Diponegoro Journal of Accounting, 2026)
The aim of this research is to examine the influence of disclosure policy and information transparency on the quality of sustainability reports, as well as to analyze the role of audit committee independence as a factor moderating this relationship.The population used in this research are all banking companies listed on the Indonesia Stock Exchange (IDX), totaling approximately 48 companies as of 2024. The data collection method employed was purposive sampling, carried out based on specific criteria, namely banking companies consistently publishing sustainability reports. The research method utilized is multiple regression analysis and Moderated Regression Analysis (MRA) with secondary data obtained from the annual reports and sustainability reports of banking companies listed on the Indonesia Stock Exchange (IDX) and supporting data from Bloomberg, covering the period of 2022–2024.The results of the analysis indicate that both disclosure policy and information transparency have a significant positive effect on the quality of sustainability reports. Furthermore, the audit committee independence is proven to strengthen the relationship, between disclosure policy and sustainability report quality, whereas it weakens the relationship between information transparency and sustainability report quality.